A Preliminary Study on the Effect of High-Power Pain Threshold Ultrasound to Desensitize Latent Trigger Points: A Double-Blinded Randomized Study. Issue 2 (June 2014) - Kim, Yushin; Kim, Jungjin; Kwak, Kun; Yoon, BumChul
Abstract Objectives: To determine the ideal number of applications of high-power pain threshold ultrasound [HPPTUS] for the desensitization of latent myofascial trigger points [LTrPs] in the elderly. Methods: Twenty-four elderly participants [65–73 years, four males, 20 females] with LTrPs identified in the upper trapezius muscle were included in the study. The participants were equally assigned to the HPPTUS-5, HPPTUS-9, and conventional US groups. The participants received five or nine times of HPPTUS or conventional US intervention to an upper trapezius myofascial TrP. Treatments were applied during three sessions for 1 week. The primary outcome variable was pressure pain threshold to evaluate the sensitivity of LTrP in the upper trapezius muscle. The secondary outcome variables were pressure pain tolerance and visual analog scale [VAS] for the subjective pressure pain intensity at 4.5 kg/cm2. Results: Between-group comparisons showed that the participants who received nine applications of HPPTUS showed a significantly greater increase in the pressure pain threshold and tolerance than the other groups at the end of the 1-week intervention. Within-group changes showed significantly decreased pain in all groups. No adverse effects were found. Conclusions: The results of this study indicate that nine applications of HPPTUS are more effective to reduce the pain sensitivity of LTrPs than conventional US techniques. Furthermore, this preliminary study showed no adverse effects of HPPTUS technique, even though strong stimulation was given to LTrPs.